Newton ring-preventing film and touch panel - TAKAHASHI HIROSHI; HAYASHI MASAKI (2012)
Disclosed is a Newton ring-preventing film whereby the occurrence of Newton rings in a resistive film-type touch panel can be effectively inhibited. The Newton ring-preventing film is produced by forming a phase separation structure, which consists of a plurality of polymers, a polymer and a curable resin precursor or a plurality of curable resin precursors, through spinodal decomposition caused by the evaporation of a solvent from a liquid phase comprising one or more polymers, one or more curable resin precursors and the solvent, and then curing said resin precursor(s) to form an anti-Newton ring layer. In this film, the aforesaid anti-Newton ring layer has a surface pattern of protrusions and recesses and isotropically transmits and scatters incident light, the scattering angle showing the maximum scattering light intensity ranges from 0.1 to 10o, and the total light transmittance ranges from 70 to 100%.